1996
DOI: 10.1007/bf00011646
|View full text |Cite
|
Sign up to set email alerts
|

Field responses to added organic matter, arbuscular mycorrhizal fungi, and fertilizer in reclamation of taconite iron ore tailing

Abstract: A three season study was conducted to determine the effect of added composted yard waste, arbuscular mycorrhizal (AM) fungi, and fertilizer on plant cover, standing crop biomass, species composition, AM fungal infectivity and spore density in coarse taconite iron ore tailing plots seeded with a mixture of native prairie grasses. Plant cover and biomass, percent seeded species, mycorrhizal infectivity and spore density were greatly increased by additions of composted yard waste. After three seasons, total plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(28 citation statements)
references
References 22 publications
1
27
0
Order By: Relevance
“…Utilization of nonmycorrhizal metal-accumulating plant species, such as T. caerulescens, although superior for extraction of excessive soil metals (8), reduces the quantity of glomalean propagules. Since AM inoculum is known to accelerate the establishment of planted vegetation (25,31,36), glomalean propagule decline may necessitate reinoculation of the site with these fungi after completion of metal phytoextraction before the desired plant cover can be established.…”
Section: Discussionmentioning
confidence: 99%
“…Utilization of nonmycorrhizal metal-accumulating plant species, such as T. caerulescens, although superior for extraction of excessive soil metals (8), reduces the quantity of glomalean propagules. Since AM inoculum is known to accelerate the establishment of planted vegetation (25,31,36), glomalean propagule decline may necessitate reinoculation of the site with these fungi after completion of metal phytoextraction before the desired plant cover can be established.…”
Section: Discussionmentioning
confidence: 99%
“…Because weedy plants usually respond better to fertilization than warm-season prairie grasses, this result may be due to increased mycorrhizal infectivity as weedy grasses did not diminish with increasing application rate but prairie grasses increased. A study conducted on iron mine tailings in Minnesota found that composted yard waste significantly increased vesicular-arbuscular mycorrhizal infectivity compared to inoculation using some of the same species planted in this study and that available P increased more in the plots amended with the compost than with fertilizers (Noyd et al 1995;Noyd, Pfleger, and Norland 1996). However, given that soil P levels only increased in the depths where pulp was incorporated, decomposition of the Fluff and subsequent mineralization of P was most likely responsible, regardless of the effect of pulp on mycorrhizal infection.…”
Section: Soil Analysismentioning
confidence: 50%
“…Whether the effect of increased plant P accumulation is a direct result of Fluff supplied P or by some other mechanism is unknown. Because weedy plants usually respond better to fertilization than warm season prairie grasses, this result may have been due to increased mycorrhizal infectivity as weedy grasses did not diminish with increasing application rate, but prairie grasses increased (Noyd et al, 1995(Noyd et al, , 1996. However, given that soil P levels only increased in the depths where Fluff was incorporated, decomposition of the Fluff and subsequent mineralization of P was most likely responsible.…”
Section: Silty-loam Soilsmentioning
confidence: 99%